1995
DOI: 10.1111/j.1476-5381.1995.tb15878.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of multiple protein kinase C isozymes in the ACTH secretory pathway of AtT‐20 cells

Abstract: 1 The mouse AtT-20/D16-16 anterior pituitary tumour cell line was used as a model system for the study of protein kinase C (PKC)-mediated enhancement of calcium-and guanine nucleotide-evoked adrenocorticotrophin (ACTH) secretion. 2 A profile of the PKC isozymes present in AtT-20 cells was obtained by Western blotting analysis and it was found that AtT-20 cells express the a, P, a and C isoforms of PKC.3 PKC isozymes were activated by the use of substances reported to activate particular isoforms of the enzyme.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
(81 reference statements)
1
10
0
Order By: Relevance
“…In an attempt to delineate the level at which glucocorticoids block PMA‐mediated signalling we examined whether PMA‐induced translocation of PKC isoforms to membrane fractions was affected in glucocorticoid‐treated cells. Previous studies in the AtT20 D16:16 cell line reported expression of the α‐, β‐ and ε‐ (PMA sensitive) as well as the ζ‐ (PMA insensitive) PKC isoforms (McFerran et al 1995). Western blotting for the PMA‐sensitive isoforms revealed robust expression of α and ε isoforms (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In an attempt to delineate the level at which glucocorticoids block PMA‐mediated signalling we examined whether PMA‐induced translocation of PKC isoforms to membrane fractions was affected in glucocorticoid‐treated cells. Previous studies in the AtT20 D16:16 cell line reported expression of the α‐, β‐ and ε‐ (PMA sensitive) as well as the ζ‐ (PMA insensitive) PKC isoforms (McFerran et al 1995). Western blotting for the PMA‐sensitive isoforms revealed robust expression of α and ε isoforms (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In AtT20 mouse corticotroph cells phorbol‐ester‐mediated activation of PKC has been proposed to exert effects both distal and proximal to voltage‐dependent calcium influx, which may result from activation of different PKC isoforms (McFerran et al 1995) to elicit ACTH release (Phillips & Tashjian, 1982; Woods et al 1992; Clark & Kempainen, 1994; McFerran et al 1995). Intracellular free calcium measurements in AtT20 cells suggest that PKC‐induced calcium influx results, at least in part, from inhibition of TEA‐sensitive potassium conductances.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PKC-was identified in the insulin-secreting cell line RINm5F (49), and recently the presence of PKC-has been demonstrated in the MIN6 ␤-cell line (52). PKC-␣, -␦, -⑀, and -predominate in the FRTL-5 thyroid cell line (32,54), and PKC-␣, -␤, -⑀, and -are found in AtT-20 cells, a mouse anterior pituitary tumor cell line (36). In primary cultures of human antral G cells, Moore et al (38) demonstrated expression of the PKC isoforms ␣, ␥, , ⑀, , and .…”
Section: Discussionmentioning
confidence: 99%
“…As an activator of the conventional (cPKC ␣, ␤ 1/2 , and ␥) and novel type PKC isoenzymes (nPKC ␦, ⑀, , and ), OAG at a concentration of 10 mol/L was used, thereby inhibiting the current at Ϫ120 mV significantly to 44.9Ϯ2.0% (nϭ4) after 30 minutes (Figure 3). Thymeleatoxin (100 nmol/L), a specific activator of the conventional protein kinase C isoenzymes, 19 was even more effective and …”
Section: Pharmacological Evidence That Pkc Mediates the Effects Of Pmmentioning
confidence: 99%